Country Risks and the Investment Activity of U.S. Multinationals in Developing Countries - Lehmann, Alexander (Washington, D.C. : International Monetary Fund, 1999)
This paper develops a simple real options model that demonstrates the role of country-specific risk and sunk costs in determining a multinational's choice between exports and foreign investment. The hypotheses from the model are tested for the distribution of capital expenditures by U.S.-owned foreign affiliates in 29 developing countries during 1984-95. Political and economic risk ratings are identified as deterrents to foreign capital formation; scale economies, unit wage differentials, trade openness, and agglomeration effects are found to be stimulating. These findings provide an additional rationale for a multilateral investment agreement that could function as an agency of restraint.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet